Confrontation or Dialogue? Productive Tensions between Decolonial and Intercultural Scholarship - Birgit Boogaard; David Ludwig; Matthias Kramm; Pius M. Mosima; Thierry Ngosso (Ergo, An Open Access Journal of Philosophy)
For several decades, intercultural philosophers have produced an extensive body of scholarly work aimed at mutual intercultural understanding. They have focused on the ideal of intercultural dialogue that is supported by dialogue principles and virtuous attitudes. However, this ideal is challenged by decolonial scholarship as one which neglects power inequalities. Decolonial scholars have emphasized the differences between cultures and worldviews, shifting the focus to colonial history and radical alterity. In return, intercultural philosophers have worried about the very possibility of dialogue and mutual understanding in frameworks that use coloniality as their singular pole of analysis. In this paper, we explore the complex relations between decolonial and intercultural philosophies. While we diagnose tensions between both intellectual discourses, we argue that these tensions turn out to be productive: for intercultural philosophers, decolonial challenges provide an opportunity to critically rethink ideals of equitable dialogue in light of colonial inequity and its deep entrenchment in global philosophical encounters. For decolonial scholars, intercultural philosophies provide an opportunity to sharpen positive proposals of equitable encounters beyond the critique of current forms of colonial domination. Rather than developing a general compromise, we propose a contextualist strategy, highlighting that different situations require different responses that can be strongly confrontational or dialogical in character. Decolonial and intercultural motifs serve different functions in the articulation of a critical global philosophy and can sharpen each other without integrating into a middle ground that is “a little bit intercultural” and “a little bit decolonial”.